TỔNG HỢP VÀ NGHIÊN CỨU PHỨC CHẤT CỦA MỘT SỐ PHỐI TỬ VÒNG LỚN KIỂU BAZƠ SCHIFF TRÊN CƠ SỞ THIOSEMICACBAZIT - Thắng, Phạm Chiến; Vân, Vũ Văn; Hải, Nguyễn Minh; Độ, Vũ Đăng (Vietnam Journal of Chemistry, 2012)
Benzilthiosemicarbazone (BzTS) has been synthesized by reacting benzil and thiosemicacrbazide in the absence of metal salt and using high dilution technique. A 12-membered macrocyclic Schiff base, 5,6,11,12-tetraphenyl-1,2,4,7,8,10-hexaaza-xiclodoeca-4,6,10,12-tetraen-3,9-dithion (LH2), was prepared from BzTS in methanol by using CuCl2 as template with fairly good yield. Alternatively, when using CuSO4 and PdCl2 in place of CuCl2 the products formed are tetradentate (N, N, N, N) macrocyclic complexes CuL and PdL. All ligands and complexes have been characterized by spectroscopic studies (IR, 1HNMR and MS). A metal – template mechanism for the formation of macrocyclic ligand and complexes was proposed.